Neural representations of popularity and leadership status relate to conformity in daily life - Ovidia A. Stanoi; Danielle Cosme; Mia Jovanova; Yoona Kang; Faustine Corbani; Amanda L. McGowan; José Carreras-Tartak; Anthony Resnick; Peter S. Bearman; Zachary M. Boyd; Dani S. Bassett; David M. Lydon-Staley; et al. (Proceedings of the National Academy of Sciences, 2026)
Individuals are motivated to increase their social status. To succeed in this pursuit, people must track information about others in their social sphere, monitor group norms, and adjust their behavior strategically. This study employed functional MRI and ecological momentary assessment methods in a sample of 92 college students belonging to 9 social groups to elucidate the neural mechanisms underlying these processes and their relationship to conformity in the context of alcohol use. When young adults passively looked at faces of their real-life social group peers, brain systems implicated in valuation and social cognition spontaneously tracked information about the popularity and leadership status of the social targets in an interdependent manner. Individual differences in these neural valuations were systematically associated with varying levels of conformity. Students who had stronger responses to faces of peers with relatively higher popularity and leadership status than themselves in one key valuation brain region, the ventromedial prefrontal cortex (vmPFC), were more likely to align their drinking behavior with their groups’ norms in everyday life. These results provide evidence for how brain systems involved in valuation and social cognition flexibly track information about peers’ popularity and leadership status in real-life social groups and contribute to a growing literature on the neural mechanisms through which social comparison processes shape conformity. Our study highlights the vmPFC as a central hub that spontaneously tracks status differences between the self and peers and uses this information to guide behavior to match group norms.